Labour and poverty in Kenya, 1900-1980 - Collier, P; Lal, D (World Bank, 1986)
Analyzes the nature of the labor market and its relationship with economic growth and income distribution in Kenya. Part 1 covers the historical evolution of the labor market from precolonial forms to a form of coercive monopsonistic organization under colonial rule over 1800-1948; the moderation of these coercive features under pressures of nationalism and humanitarian impulses over 1948-68; and the correction during 1968-80 of certain policy induced distortions. Presents an account of major events and decisions in each period and examines their impact on wage and employment trends and patterns. Part 2 analyzes these trends in terms of the predictions of "experts" and argues that an efficient poverty-redressing program involves the growth of smallholder agriculture and skill formation of the urban labor force. Discusses policy induced distortions in rural-urban wages, their impact on migration, unemployment, and urban poverty, and overall growth. Collier is a Fellow of Keble College, Oxford University. Lal is Professor of Political Economy, University College, London. Bibliography; index.